Reexame de prova em recurso especial - Costa, Henrique Araújo (2006)
The subject addressed by the present text is the evidence reexame in an appeal to the Brazilian Superior Court of Justice. The topic under epistemological and dogmatic points of view retakes the concepts of fact and norm to critically analyze the court decisions in the application of its seventh abridgement that states: "The pretension of simple evidence reexame does not try the appeal to the Superior Court of Justice". Therefore, is applied an epistemological and procedural retrospect, from Roman Law to nowadays Instrumentalism, questioning the current landmark of analysis. Under a dogmatic boarding it is cogitated the possibility of setting distinctive criterias of fact and norm concepts, concluding for its impossibility, especially if anchored in the subsumetive paradigm. The present text, based on the Knijnik´s Tricotomic Theory and its concept of mixed questions, attempts to overcome the subsumetive paradigm. However, it concludes that the Tricotomic Theory tackles in an artificial division of concepts. As contribution for a new dogmatic, the present text offers a linguistic and discursive approach of the subject. In support to this approach, axiology and semiotics are binded towards a rhetorical reconstruction, that reread after-modern fashion offers a chance of reflection under more current argumentative and systematic prisms to the procedural thought. After these retaken cases are analyzed it is possible to isolate and criticize emblematic examples of the incompatibility involving the theory of the common sense of the procedure (subsumitive and binary) in contrast with the court decisions (rhetorical and complex).